Unit and internal chain profile of African rice (Oryza glaberrima) amylopectin. (10th February 2016) - Gayin, Joseph; Abdel-Aal, El-Sayed M.; Manful, John; Bertoft, Eric
Highlights: The detailed structure of African rice amylopectin was investigated. The distribution of chains in African rice amylopectin is similar to Asian rice. The external chains of African rice amylopectin are longer compared to Asian rice. The short chains of amylopectin correlated with thermal and pasting properties. African rice amylopectin belongs to the similar structural type as maize. Abstract: High-performance anion-exchange chromatography was used to study the unit chain profiles of amylopectins and their φ, β-limit dextrins from two African rice ( Oryza glaberrima ) accessions—TOG 12440 and IRGC 103759. The samples were compared with two Asian rice ( Oryza sativa ) samples (cv Koshihikari and cv WITA 4) and one O. sativa × O. glaberrima cross (NERICA 4). The ratio of short:long chains ranged between 12.1 and 13.8, and the ratio of A:B-chains was ∼1.0 in all samples. A significant difference was observed in the distribution of internal chains with regards to the proportion of short "fingerprint" B-chains (Bfp -chains), which in the φ, β-limit dextrins have a degree of polymerization (DP) 3–7. The African rice starches and NERICA 4 had higher levels of Bfp -chains, but the major group of short B-chains (DP 8–25) was similar to that of the Asian rice samples. The average chain length (CL), internal chain length (ICL), and total internal chain length (TICL) were similar in all samples. However, the external chain length (ECL) was longer in the African rice samples and NERICA 4. ECL correlated positively and significantly ( p < 0.05) with gelatinization transition temperatures and enthalpy suggesting differences between the two rice types in cooking properties.